Fungsi Ekonomis dan Yuridis Kontrak dalam Perspektif Hukum Bisnis - Syamsul Munir (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2020)
In the legal relationship in the era of increasingly advanced busines straffic, it requires a legal framework that can paralyze evil lust to cause harm to one party. It must be understood by business people or others about the legal terms of the agreement and held as a guide if making a contract. This discussion will focus on the Legal Function of Contracts in the perspective of business law and the economic function of Contracts in the perspective of business law. The juridical function of the contract is designed to realize legal certainty for the parties making the contract and for the third parties involved in the contract. The economic function of the contract guarantees that the mutual expectations between the parties will be fulfilled or compensation will be paid in the event of default.